(untitled) (Global Journal of Medical Research, 2014)
Trichopus zeylanicus Gaertn. (Dioscoreaceae) [TZ] leaf is traditionally used as a general health tonic in tribal regions of south India. In the present study the effect of alcoholic extract of TZ leaves was evaluated on acute stress induced anxiety in mice at oral doses of 100mg/kg, 250mg/kg and 500mg/kg. Acute stress was induced by restraint stress method and the stressed rodents were evaluated in light and dark model and elevated plus maze. The extract at the doses of 250mg/kg and 500mg/kg showed a significant increase in the number of crossings and reduced time spent in the dark chamber in light and dark model. Further, it significantly reduced the time spent in the closed arm in elevated plus maze as compared to stressed mice. Moreover, TZ significantly reduced stress induced increased plasma corticosterone levels and hyperglycemia in rats.